Transforming Spaces into Places: Placemaking of Tudikhel - Parajuli, Navin (Journal of Advanced College of Engineering and Management, 2022)
In the process of planning and developing public spaces in cities, place-making is a people-centered approach. This approach considers the perspectives of the people who live in a given location in order to learn about their needs and goals for that location or particular space. In this research, both qualitative and quantitative methods are used to find out the perception of people towards Tudikhel. Data collected from questinnare survey of the people under various categories around Tudikhel involves qualitative aspects of the research. Under quantitative approach, the key variables of the study are correlated with each other to find the strength of relationship between the variables. Finally, suitable conclusions are reached regarding strategies including elements and activities of placemaking at Tudikhel. Hence this study emphasizes in restoring of Tudikhel back to ‘place’ in the contemporary urban context using the activities and elements of placemaking, to ensure the sustainability of Tudikhel as a national public space of Nepal.